Label Halal dan Hukum Asal Bahan Pangan - Arif Al Wasim (Syariati: Jurnal Studi Al-Qur'an dan Hukum, 2016)
The consumption of halal is one of the important suggestions of the Sharia for Muslims. Nowadays, public awareness of the importance of halal consumption is increasing. The guarantee of foodstuffs in Indonesia is halal certificates and labels as regulated in Undang-Undang No. 33 tahun 2014 on Guarantee of Halal Products. Not all of food products circulating and distributed in Indonesia has halal certificates and labels. This study was conducted to assess the assurance of halal food that does not have halal certificates and labels, and how to consume it in dealing with the law of sharia. The study was conducted with approach of Jurisprudential Rules (Qawâ’id Fiqhiyyah), focusing the discussion of the status of "legal origin" and it’s continuity of the validity on the foodstuffs, and to what extent the effectiveness of the halal certificates and labels toward the guarantee of halal food. Conclusions from the study shows that the “legal origin” of food is halal and it is still valid as long as no valid and explicit information nor indications that is prohibited. In case of consuming foods that are halal in origin, but it is unknown the halal assurance, no need to complicate by questioning the validity and legality of its halal status. By affirming the confidence and steadiness and accompanied by reading Basmalah is enough to be a halal guarantee of food consumed.